Employee Loyalty Is Reviewed From Compensation, Work Environment, and Workload through Job Satisfaction - Prabowo, Heri; Dhari, Agita Wulan; Violinda, Qristin (PT. Riset Press International, 2025)
This research was conducted to determine the effect of compensation, work environment, and workload on employee loyalty through job satisfaction at Hotel Neo Candi Simpanglima Semarang. The study adopted a quantitative approach. The population consisted of employees at Hotel Neo Candi Simpanglima Semarang. In this research, the researcher used non-probability sampling with a saturated sampling method (census). Data were collected from 150 respondents using a questionnaire. The data were processed using Smart PLS 3. The research findings are as follows: Compensation does not affect job satisfaction at Hotel Neo Candi Simpanglima Semarang. The work environment does not affect Hotel Neo Candi Simpanglima Semarang's job satisfaction. The workload does not affect job satisfaction at Hotel Neo Candi Simpanglima Semarang. Job satisfaction positively and significantly affects employee loyalty at Hotel Neo Candi Simpanglima Semarang. Compensation positively and significantly affects employee loyalty at Hotel Neo Candi Simpanglima Semarang. The work environment positively and significantly affects employee loyalty at Hotel Neo Candi Simpanglima Semarang. Workload positively and significantly affects employee loyalty at Hotel Neo Candi Simpanglima Semarang. Compensation positively and significantly affects employee loyalty through job satisfaction at Hotel Neo Candi Simpanglima Semarang. The work environment positively and significantly affects employee loyalty through job satisfaction at Hotel Neo Candi Simpanglima Semarang. Workload positively and significantly affects employee loyalty through job satisfaction at Hotel Neo Candi Simpanglima Semarang.